1993
DOI: 10.2136/sssaj1993.03615995005700060027x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effects of No‐Till Crop Residues on Corn Yield and Nitrogen Uptake

Abstract: The residual effects of crop residues on N availability and crop growth are largely unknown. A field experiment was conducted from 1986 through 1988 at Lincoln, NE, to determine the residual effects on no‐till corn (Zea mays L.) production and N uptake of 0, 50, 100, and 150% of the amount of crop residues produced by the previous crop during the previous 5 yr. These effects were evaluated with and without tillage (disking), N fertilizer (60 kg N ha−1), and hairy vetch (Vicia villosa Roth ssp. villosa, ‘Madiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 20 publications
3
37
2
4
Order By: Relevance
“…These desirable outcomes of residue retention, some of which take several years to become evident, have been reported extensively for other mainly temperate environments (Blevins and Frye, 1993;Karlen et al, 1994). Effects of crop residue amount were sometimes modified by other management practices such as type of tillage and crop fertilization and, use of cover crops (Maskina et al, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…These desirable outcomes of residue retention, some of which take several years to become evident, have been reported extensively for other mainly temperate environments (Blevins and Frye, 1993;Karlen et al, 1994). Effects of crop residue amount were sometimes modified by other management practices such as type of tillage and crop fertilization and, use of cover crops (Maskina et al, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…With regard to sustainability of the soil resources, removing stalks very close to the soil surface will result in less surface residue cover, exacerbate the potential wind and water erosion [10][11][12], accelerate the decline in soil organic carbon levels [13,14], and potentially reduce future crop yields [15]. More detailed discussions of potential impacts of stover removal on future productivity and soil quality are presented by Wilhelm et al [16], Wilts et al [17], and Kim and Dale [18].…”
Section: Article In Pressmentioning
confidence: 99%
“…Larson et al (1972) showed that SOC was linearly related to the quantity of residue added, but establishing a direct linkage between stover harvest and subsequent grain yield is difficult. Some studies have shown that residue removal reduces grain and stover yield in subsequent crops (Wilhelm et al, 1986) and further lowers SOC levels (Clapp et al, 2000;Maskina et al, 1993), but others have shown either no effect or even increases in subsequent grain yields (Karlen et al, 2011). Lal (2004a and Wilhelm et al (2004Wilhelm et al ( , 2007 concluded that returning a portion of the crop residue to soils was crucial for replenishing SOC and that doing so was a fundamental requirement for sustainable soil and crop management.…”
Section: Introductionmentioning
confidence: 99%